Model of instructional strategy based on the brain’s natural learning system in inclusive classrooms: special teacher perceptions - et al., Rasmitadila (International Journal of Advanced Science and Technology, 2020)
The problems faced by a special teacher (ST) in achieving the success of learning for students with special needs (SNS) is the difficulty of finding effective instruction that can meet the needs of SNS with typical characteristics. The purpose of this study is to explore ST’s perceptions of the instructional strategy model based on the brain’s natural learning system in inclusive classroom of primary school. The study involved seven of STs’ primary school which came from several inclusive primary schools in several cities in Indonesia. Data were collected by classroom observation and open interviews in inclusive classrooms using instructional strategy model based on the brain’s natural learning system. Data were analyzed using qualitative data analysis. The research produced five main themes consisting of student learning motivation, student learning experience, student social skills, students’ talents and interests, and ST competencies. In the end, this research has contributed that ST can develop competencies that can be used in assisting SNS in instruction, and directly the benefits can be felt by SNS both academically and non-academically. Instructional strategy model based on the brain’s natural learning system can be used as a model in managing inclusive classrooms by ST, together with general teachers (GT), to be more effective.